Angularly resolved RABBITT using a second harmonic pulse. (16th October 2017) - Loriot, Vincent; Marciniak, Alexandre; Karras, Gabriel; Schindler, Baptiste; Renois-Predelus, Gina; Compagnon, Isabelle; Concina, Bruno; Brédy, Richard; Celep, Gulabi; Bordas, Christian; Constant, Eric; Lépine, Franck
Abstract: Processes in atoms or molecules on the attosecond timescale have been measured using XUV attosecond and IR femtosecond pulses overlapping in time and controlled with attosecond accuracy. Within this general framework, many strategies have been developed using the harmonics of the fundamental pulse. In this paper, we focus on a specific configuration where the attosecond pulse train is composed by odd harmonics and is dressed by the second harmonic of the fundamental light. Measuring the angularly resolved photoelectron spectrum as a function of the delay between the pulses, a clear oscillation of the anisotropy parameters appears revealing attosecond controlled interferences. This process, is assigned to interferences between two quantum paths involving one XUV photon, on one path, and a XUV+UV photons on the other path. The XUV-UV delay dependent up–down asymmetry can be interpreted following the usual RABBITT formalism, where the dressing photon energy corresponds to the energy separation between the XUV photons of the attosecond pulse train. This approach allows an intuitive analysis of the interference and provides a well suited method for the study of complex valence band systems thanks to the limited congestion of the resulting spectrum.